Adefovir Dipivoxil Alone or in Combination with Ongoing Lamivudine in Patients with Decompensated Liver Disease and Lamivudine-resistant Hepatitis B Virus - Kim, Kang Mo (The Korean Academy of Medical Sciences, 2005)
The purpose of this prospective study was to evaluate the efficacy and safety of adefovir dipivoxil with or without ongoing lamivudine in decompensated lamivudine-resistant chronic hepatitis B patients. Forty-six hepatitis B e antigen (HBeAg)-positive patients with decompensated liver function and lamivudine-resistant hepatitis B virus (HBV) were assigned to adefovir dipivoxil monotherapy (n=18) or combination therapy with ongoing lamivudine (n=28) according to their own preference. After 24 weeks of treatment, 83% of monotherapy and 86% of combination therapy showed serum HBV DNA below detection limit (<0.5 pg/mL). Alanine aminotransferase (ALT) normalized in 78% and 82% respectively. Median Child-Pugh-Turcotte (CPT) score or Model for End-Stage Liver Disease (MELD) score reduced significantly by 3 or 5 point in monotherapy and 2 or 2 point in combination therapy respectively. There were no significant differences in rate of undetectable serum HBV DNA, median change of ALT and median reduction of CPT or MELD scores between the two groups. In conclusion, both adefovir dipivoxil monotherapy and combination therapy with ongoing lamivudine result in comparable virologic, biochemical, and clinical improvements in HBeAg-positive patients with decompensated liver function and lamivudine-resistant HBV. Combination with lamivudine showed no additional benefit over monotherapy during 24 weeks of treatment in these patients.